Needs Analysis in EFL: A Literature Based Study on Necessities, Lacks, and Wants for Materials Development - Salmah Salmah; Shella Aulia Putri; Zahra Ichtiara Massari; Hesty Widiastuty (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This literature-based study aims to synthesize theoretical and methodological perspectives on needs analysis (NA) in English as a Foreign Language (EFL), emphasizing the framework of necessities, wants, and lacks (NWL) and its implications for materials development. A total of twenty-five peer-reviewed journal articles (2010-2024), three seminal books, and two policy documents were analyzed through thematic and comparative methods. Sources were selected based on their relevance to EFL contexts, academic credibility, and contribution to materials design. The review reveals three key findings. First, needs analysis serves as a cornerstone in curriculum and materials development, ensuring instructional relevance and learner engagement. Second, the NWL framework remains conceptually robust, though its application requires methodological diversification through triangulation of questionnaires, interviews, and observations. Third, digital tools and technology-enhanced approaches have revitalized NA practices, promoting dynamic and data-driven insights into learners’ needs. Conceptually, this study bridges classical and contemporary perspectives on NA. Practically, it offers guidance for teachers, curriculum designers, and material developers to integrate systematic and evidence-based needs analysis into EFL instructional design.